Pengaruh Modal Pinjaman dan Kredit Bermasalah terhadap Profitabilitas - Nugroho, Gatot Wahyu; Nurodin, Idang; Artiamara, Mutia (Universitas Muhammadiyah Tangerang, 2023)
This study aims to: (1) Explain the effect of loan capital on profitability. (2) Explaining the effect of non-performing loans on profitability. (3) Explaining the effect of loan capital and non-performing loans on profitability. The variables used in this study are Loan Capital (X1), Non-performing Loans (X2), Profitability (X3). This research was conducted at the Citra Utama Credit Cooperative for the 2016-2020 period. The sampling technique in this study used a purpose sampling technique. Sources of data used are secondary data sources obtained by means of documentation and literature study.The data analysis used is non-parametric with classical assumption test in this study is normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis. Hypothesis test using t test, f test, and coefficient of determination. With the results of the research loan capital has no effect on profitability with the significance of the loan capital variable (X1) 0.073 > 0.05 and tcount < ttable (-1.852 < 2.002), non-performing loans have a negative effect on profitability with the significance of loan capital variable (X1) 0.044 > 0 .05 and tcount > ttable (-2.056 < 2.002), Loan capital, non-performing loans have a simultaneous effect on profitability with a significance of 0.072 > 0.05 Fcount that is 2.756 > Ftable 3.16.Keywords: Loan Capital, Non-performing Loans, Profitability